2020
DOI: 10.1002/cbic.201900741
|View full text |Cite
|
Sign up to set email alerts
|

Cyp1 Inhibition Prevents Doxorubicin‐Induced Cardiomyopathy in a Zebrafish Heart‐Failure Model

Abstract: Doxorubicin is a highly effective chemotherapy agent used to treat many common malignancies. However, its use is limited by cardiotoxicity, and cumulative doses exponentially increase the risk of heart failure. To identify novel heart failure treatment targets, a zebrafish model of doxorubicin‐induced cardiomyopathy was previously established for small‐molecule screening. Using this model, several small molecules that prevent doxorubicin‐induced cardiotoxicity both in zebrafish and in mouse models have previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Therefore, CYP2J2 may not be a reasonable therapeutic target in cardio-oncology. On the other hand, CYP1A1 has been shown to contribute to both anthracycline-induced cardiotoxicity [110][111][112][113] and tumor progression and survival of cancer cells [114,115]. Therefore, similar to CYP1B1, CYP1A1 may also be a reasonable therapeutic target in cardio-oncology.…”
Section: Role Of Cyp1b1 In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CYP2J2 may not be a reasonable therapeutic target in cardio-oncology. On the other hand, CYP1A1 has been shown to contribute to both anthracycline-induced cardiotoxicity [110][111][112][113] and tumor progression and survival of cancer cells [114,115]. Therefore, similar to CYP1B1, CYP1A1 may also be a reasonable therapeutic target in cardio-oncology.…”
Section: Role Of Cyp1b1 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Although this lack of selectivity toward CYP1B1 may be undesirable from a mechanistic point of view, it may offer a therapeutic advantage since CYP1A1 is also a reasonable target in cardio-oncology as discussed earlier. Indeed, a number of studies have reported a protective effect of CYP1 inhibitors without discerning the protective effects to either CYP1A1 or CYP1B1 [112,113]. That being said, 2,4,3 ,5 -tetramethoxystilbene (TMS) exhibited 50-fold selectivity for CYP1B1 over CYP1A1 and 500-fold selectivity for CYP1B1 over CYP1A2 [146].…”
Section: Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…An example of a cardiotoxic agent is doxorubicin, a highly effective chemotherapy drug, the use of which is limited by cumulative, dose-related myocardial damage which can lead to heart failure. Using a zebrafish model of doxorubicin-induced cardiomyopathy for small-molecule screening, cytochrome P450 family 1 (CYP1) has been recently identified as a candidate therapeutic target for clinical cardioprotection 148,149 . Zebrafish, first introduced as a developmental model in 1970s, have become an increasingly attractive and valuable model for studying human diseases.…”
Section: Cardiovascular Drug Discovery and Future Directionsmentioning
confidence: 99%
“…Acute doxorubicin toxicity has been particularly well studied in zebrafish, whereby a dose of doxorubicin 100 μM added to the embryo medium results in pericardial edema, decreased blood flow through the tail vasculature, and decreased cardiac contractility that can be visualized using a standard light microscope [ 7 ]. Our laboratory used this model to identify Cytochrome P450 Family 1 enzymes as an important therapeutic target in anthracycline cardiomyopathy [ 8 , 72 ], not only in acute cardiotoxicity but also in chronic doxorubicin cardiomyopathy models in adult mice. A chronic model of doxorubicin cardiomyopathy has also been developed in adult zebrafish, whereby hearts from fish treated with doxorubicin exhibited myofibril disarray and fetal cardiac gene expression [ 73 ].…”
Section: Zebrafish As a Model For Cancer Therapy-associated Cardiomentioning
confidence: 99%
“…Genetic knockout models can be created to investigate a cardiotoxic drug’s mechanism of action and target. For instance, a chemical screen in zebrafish enabled the identification of Cyp1 enzymes in anthracycline cardiotoxicity, and mutation of the Cyp1 active site using CRISPR/Cas9 prevented the development of cardiotoxicity in fish [ 72 ]. One could envision using zebrafish to study variants associated with cardiotoxicity in human genome-wide association studies.…”
Section: Zebrafish As a Model For Cancer Therapy-associated Cardiomentioning
confidence: 99%